Oral medicinal cannabinoids to relieve symptom burden in the palliative care of patients with advanced cancer: a double-blind, placebo-controlled, randomised clinical trial of efficacy and safety of 1:1 delta-9-tetrahydrocannabinol (THC) and cannabidiol (CBD) - Hardy, Janet; Haywood, Alison; Gogna, Gauri; Martin, Jennifer; Yates, Patsy; Greer, Ristan; Good, Phillip (Current controlled trials in cardiovascular medicine, 2020)
Background Despite improvements in medical care, patients with advanced cancer still experience substantial symptom distress. There is increasing interest in the use of medicinal cannabinoids but little high-quality evidence to guide clinicians. This study aims to define the role of a 1:1 delta-9-tetrahydrocannabinol/cannabidiol (THC/CBD) cannabinoid preparation in the management of symptom burden in patients with advanced cancer undergoing standard palliative care. Methods and design One hundred fifty participants will be recruited from five sites within the Queensland Palliative Care Research Group (QPCRG) and randomly assigned to an active treatment or placebo group. This study is a pragmatic multicentre, randomised, placebo-controlled, two-arm trial of escalating doses of an oral 1:1 THC/CBD cannabinoid preparation. It will compare efficacy and safety outcomes of a titrated dose (10 mg/10 mg/mL oral solution formulation, dose range 2.5 mg/2.5 mg–30 mg/30 mg/day) against placebo. There is a 2-week patient-determined titration phase, using escalating doses of 1:1 THC/CBD or placebo, to reach a dose that achieves symptom relief with tolerable side effects. This is then followed by a further 2-week assessment period on the stable dose determined in collaboration with clinicians. The primary objective is to assess the effect of escalating doses of a 1:1 THC/CBD cannabinoid preparation against placebo on change in total symptom score, with secondary objectives including establishing a patient-determined effective dose, the change in total physical and emotional sores, global impression of change, anxiety and depression, opioid use, quality of life and adverse effects. Discussion This will be the first placebo-controlled clinical trial to rigorously evaluate the efficacy, safety and acceptability of 1:1 THC/CBD for symptom relief in advanced cancer patients. This study will allow the medical community to have some evidence to present to patients wishing to access cannabis for their symptoms caused by advanced malignancy. Trial registration ACTRN, ACTRN12619000037101 . Registered on 14 January 2019. Trial Sponsor: Mater Misericordiae Limited (MML) and Mater Medical Research Institute Limited (MMRI)—Raymond Terrace, South Brisbane, Brisbane, QLD, Australia